Determination of the Enzymatic Kinetics of Polyphenoloxidase in Different Coffee Varieties of Ecuador - Felipe, Jadán Piedra; Carlos, Jadán Piedra (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
In this work, the enzymatic kinetics of Polyphenoloxidase (PPO) in different varieties of Arabica coffee (Typico, Caturra and Salchimor) was studied. The optimum pH and temperature of the PPO, the enzymatic activity (U) and the Michaelis – Menten constant were evaluated. To determine the enzymatic activity the JENWAY 7305 UV- Vis spectrophotometer with a wavelength of 410 nm was used. The optimum temperature and pH of the PPO were found to be 50 and 7.0 respectively, being constant in the coffee varieties studied. The affinity of the enzyme for the substrate as well as the activity of the PPO was studied using catechol as a substrate. The results in the different varieties were: Typical (KM=0.622 mM; and 6234.32 U/mL) Salchimor (KM= 0.822 mM; and 5612.10 U/mL) and Caturra (KM= 0.933 mM and 3710.86 U/mL). Finally, the oxidation of catechol (substrate) was evaluated by observing the time of disappearance that was set at 160 seconds for the variety with the highest activity.